Surface Damage and Bleaching Effect according to the Application Type of Home Tooth Bleaching Applicants - Na-Yeoun Tak; Do-Seon Lim; Hee-Jung Lim; Im-Hee Jung (치위생과학회지, 2020)
Background: In this study, the bleaching effect and surface damage of two types of over-the-counter home tooth bleaching agents were explored using an in vitro study of bleaching agents applied to bovine teeth specimens for 14 days.Methods: Domestic over-the-counter home tooth bleaching agents of gel and patch form that shared common active ingredients and manufacturers were selected and tested. The experiment specimens were made using composite resin with bovine tooth samples and then measured the initial microhardness. Specimens were then divided into a Gel group and a Patch group and underwent bleaching treatment once a day for two weeks for 30 to 60 minutes (recommended) or 7 hours. All specimens were coffee-stained prior to bleaching. The bleaching effect was measured using a spectrophotometer and surface damage was measured using a microhardness meter.Results: The difference in color following the bleaching procedure was positive in both the Gel and Patch group, although there were no statistically significant differences in bleaching effect between groups. There was no significant difference in bleaching effect based on duration. The microhardness test revealed that both the Gel group and the Patch group had surface damage after bleaching. The greatest surface damage was found in the Patch group that had undergone a 7-hour bleaching treatment, although the differences were not statistically significant.Conclusion: The bleaching effect of the home tooth bleaching agent was visible to the naked eye. However, longer applications than recommended did not result in greater bleaching, unlike consumers’ expectations, and instead increased the chance of enamel damage. As such, there is a need for consumers to be alert and adhere to recommendations provided by each company.